Higgs and Vector Unparticle Production via Collision in the Randall – Sundrum Model - Thi Hau, Nguyen; Thuy, Dao Thi Le (VNU Journal of Science: Mathematics - Physics; Vol 35 No 4DO - 10.25073/2588-1124/vnumap.4375, 2019)
This paper studies the production of Higgs boson and vector  unparticle, which has been proposed as an option for collision by s, t, u-channels in the Randall-Sundrum model. The cross-section is presented and numerical evaluation is detailed. The study results reveal that the cross-section increases as fast as . The advantageous directions to collect Higgs boson and  are either the same or opposite to the initial muon beams by s-channel. The  exchange contribution is much larger than muon exchange contribution .